Advances in bioconversion of spent tea leaves to value-added products. (February 2022) - Negi, Taru; Kumar, Yogesh; Sirohi, Ranjna; Singh, Shikhangi; Tarafdar, Ayon; Pareek, Sunil; Kumar Awasthi, Mukesh; Alok Sagar, Narashans
Graphical abstract: Highlights: Pre-treated spent tea leaves (STL) are good carbon sources for fermentation. Biopolymer, bioactive compounds, biochar and biofuels, currently produced using STL. Catalytic gasification can be used to produce bioenergy from STL more efficiently. STL protein and carbohydrate can be explored for peptide polysaccharide production. Nanocatalysts, battery electrodes and biofilters are trending applications of STL. Abstract: Spent tea leaves (STL) are generated after the extraction of liquor from processed tea leaves and are regarded as an underutilized waste. STL are rich in essential amino acids, ω-6 and ω-3 fatty acids, alkaloids (theobromine and caffeine), polyphenols (catechin, theaflavins and rutin) and minerals (Ca, P, K, Mg, Mn) that could be utilized for the production of industrially important products. Vermicomposting, anaerobic digestion, silage preparation and fermentation are currently used as low cost methods for the bioconversion of STL to a usable form. Structural, morphological and chemical modification of STL after suitable bioconversion enables its application in the development of biopolymers, biofuels, catechin derivatives, biochar, absorbents for dye, and for removal of Cd, Hg, Cr(IV), As(V) and aspirin. This review discusses the composition, characterization, bioconversion and value added product generation from STL while highlighting prospective applications of STL in developing battery electrodes, nanocatalysts, insulation materials and edible bioactive peptides.